Shifts in the antibiotic susceptibility profiles of zoonotic enteric bacteria in response to long-term chlortetracycline usage for the control of bovine anaplasmosis - Bickmeier, Naemi Pomwenepawa (My University, 2025)
Antibiotic resistance is a global crisis with serious consequences for public health, animal health, food security, and economies. Prolonged antibiotic use is a major driver of antibiotic resistance. Bovine anaplasmosis, a globally prevalent, economically significant tick-borne disease of cattle, is commonly controlled through long-term use of chlortetracycline (CTC) medicated feed at dosages of 0.5-2.0 mg/lb BW/day for six months or more. The goal of these studies was to determine if administering CTC at different dosages to control active anaplasmosis in steers promotes antibiotic resistance in off-target zoonotic bacteria, E. coli and Enterococcus. We hypothesized that feeding steers CTC for 120 days would increase the recovery of tetracycline (TET)-resistant E. coli and Enterococcus isolates, with resistance occurring more rapidly in groups receiving higher CTC doses. Additionally, we anticipated that TET resistance would co-select for resistance to other antibiotics not administered during the study. Cattle chronically infected with Anaplasma marginale were assigned to one of four CTC treatment groups: 0.0-, 0.5-, 2.0-, and 10.0 mg/lb BW/day, and fed their respective CTC rations. Single E. coli (n=192) and Enterococcus (n=222) isolates were obtained from each steer 12 days prior to CTC administration, after 58 and 114 days of continuous CTC administration, and 21 days post-cessation of CTC administration. Antibiotic susceptibilities were assessed using Clinical & Laboratory Standards Institute (CLSI) or the National Antimicrobial Resistance Monitoring System (NARMS) breakpoint classifications. Data analyses were performed using linear mixed model analysis with [alpha] = 0.10. For E. coli, there was a significant CTC effect on tetracycline TET minimum inhibitory concentration (MIC) (p = 0.089). Against a panel of 2,688 (192 isolates * 14 antibiotics) antibiotics tested , 18.0% were resistant. Resistance generally increased with higher CTC doses: 95, 116, 115, and 152 resistant tests in the 0.0, 0.5, 2.0, and 10.0 mg groups, respectively. Resistance increased during CTC administration and slightly decreased after withdrawal. Overall, 84% of isolates were resistant to at least one antibiotic, and 50.5% were multidrug-resistant. TET resistance was observed in 78.6% of isolates, with 58.8% of isolates resistant before CTC administration. While TET MIC values did not differ significantly among treatment groups (p ≤ 0.266), the proportion of TET-resistant isolates increased during treatment. Significant CTC effects were also observed for chloramphenicol (CHL) and streptomycin (p = 0.012 and p = 0.029, respectively), with MIC values crossing breakpoint classifications during CTC administration and slightly decreasing post-cessation of CTC administration. For Enterococcus, against a panel of antibiotics, the total number of resistant MIC tests was 71 (n=714), 64 (n=756), 70 (n=840), and 77 (n=738) for the groups 0.0-, 0.5-, 2.0- and 10.0 mg, respectively. Ninety-six isolates were resistant to at least one antibiotic, while 5.0% were multidrug-resistant. TET resistance was observed in 89.6% of isolates overall, with 93.0% resistant prior to CTC administration. No significant CTC effect was found on TET MIC values (p >̲ 0.1153). Additionally, there was no evidence that CTC use promoted resistance to other antibiotics tested. These studies demonstrate a high inherent TET resistance in both E. coli and Enterococcus isolates from steers. Furthermore, CTC administered at 0.5–2.0 mg/lb BW/day may promote resistance to non-tetracycline antibiotics in E. coli, but not in Enterococcus. Given that field use of CTC often exceeds 120 days, the resistance patterns observed here may be even more pronounced in real-world conditions. These results underscore the urgent need for non-antibiotic alternatives to control bovine anaplasmosis, such as an effective, strain-independent vaccine.
Keywords: Antibiotic resistance; Bovine anaplasmosis; Anaplasma marginale; Co-resistance; Cross-resistance; Minimum inhibitory concentration